Deterioro cognitivo en las actividades instrumentales de la vida diaria, en los adultos mayores de la Unidad de Atención Domiciliaria MMA Guano El Rosario del MIES - Yambay Vilema, Miguel Andrés (2020)
The main objective of the present research was to determine the cognitive impairment in the instrumental activities of daily life, of older adults of the home care unit mission My Best Years (MMA) located in the Province of Chimborazo, Canton Guano el Rosario of the Ministry of Economic and Social Inclusion (MIES) Taking into account that cognitive impairment in the elderly is the process of decreased performance of intellectual or cognitive functions, represents a difficulty in processing thoughts, making decisions and promotes a high level of deconcentration, establishing itself as a condition that manifests itself in different degrees, from mild to moderate to dementia. The methodology used for the execution of the present investigation was a non-experimental design, due to the objectives; field and cross-sectional, with a descriptive level, the population was the elderly from the MMA Guano el Rosario home care unit of the MIES, their intentional non-probabilistic sampling below, 34 Elderly adults, the mini mental state examination instruments, scale Lawton and Brody geriatric scale, Yesavage geriatric scale, Barthel index, through which it was possible to identify that 29% have mild cognitive impairment, 9% mild, 18% moderate, 44% normal, reaching the conclusion It has been possible to investigate that older adults present different degrees with respect to cognitive impairment, since they can still carry out various activities by themselves, both basic and instrumental.